2018
DOI: 10.3390/en11123296
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Demand Response Aggregators and the Effect of GenCos Strategic Bidding on the Flexibility of Demand

Abstract: This paper presents an interactive trading decision between an electricity market operator, generation companies (GenCos), and the aggregators having demand response (DR) capable loads. Decisions are made hierarchically. At the upper-level, an electricity market operator (EMO) aims to minimise generation supply cost considering a DR transaction cost, which is essentially the cost of load curtailment. A DR exchange operator aims to minimise this transaction cost upon receiving the DR offer from the multiple agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In Reference [22], a renewable-based power generation multi-objective robust scheduling methodology was presented, to lessen the effects of uncertainties on the proposed system's stable operation. A bi-level hierarchical decision-making was published in Reference [23], to specify the character of DRA and GenCos bidding strategy on the adaptability of loads. An upper level of the proposed problem in Reference [23] is minimizing generation costs, as well as the cost of demand curtailment.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [22], a renewable-based power generation multi-objective robust scheduling methodology was presented, to lessen the effects of uncertainties on the proposed system's stable operation. A bi-level hierarchical decision-making was published in Reference [23], to specify the character of DRA and GenCos bidding strategy on the adaptability of loads. An upper level of the proposed problem in Reference [23] is minimizing generation costs, as well as the cost of demand curtailment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the suggested modifications, it is also important to consider the issue of remuneration for other services provided by the microgrid, such as the supply of reactive power and the availability of its installed power to be cut by the utility in case of grid overload, representing a service as demand response. For these services, they may be paid by the utility through bilateral agreements as already in practice in some countries in case of demand response [8]. Thus, the utility may offer a monthly fee for providing active or reactive power and pay an hourly rate when this service is actually requested by the utility.…”
Section: Other Considerationsmentioning
confidence: 99%
“…The design of these tariffs should consider a fair division of the value and costs created by the microgrid. However, it is concluded that this return should be defined by utilities wishing to implement a demand-side management program once the program is structured [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ignition of these fossil-fuels produce about 78.5 metric tons of carbon-di-oxide. Furthermore, CO2 emission is intensifying everyday as energy usage rate is increasing for population growth and fast economic advancement [6][7][8]. A determined target was set to produce 2470 MW and 3864 MW electricity by 2021 and 2041 respectively from renewable resources according to the final report of power system Master plan 2016 of Bangladesh government [9].…”
Section: Introductionmentioning
confidence: 99%